Mannose-resistant adhesion of motile Aeromonas to INT407 cells and the differences among isolates from humans, food and water. - Nishikawa, Y. (Cambridge University Press, 1991)
Aeromonas has been recognized as an important enteropathogen, but factors related to its virulence have not been clarified. For most enteric pathogens, attachment is a prerequisite for infection and for the effective delivery of toxins to the intestinal epithelial cells. We examined a total of 273 strains isolated from stool, food and environmental specimens by an assay for mannose-resistant adhesion to INT407 cells in vitro. Seventeen of the 102 faecal isolates were adhesive strains with more than 10 bacteria adhering per cell, while only 2 of the 118 isolates from foods and river water adhered to the cells (P less than 0.001). It is possible that the adhesion might serve as a marker for discrimination between the pathogenic and nonpathogenic isolates. The 8 highly adhesive strains with more than 20 adhering organisms per cell were scrutinized for the mechanism of adhesion. No correlation was apparent between the adhesion to INT407 cells and hydrophobicity. It was noted that fucose inhibited the adhesion of four strains as well as haemagglutination by them. Electronmicroscopic studies showed the presence of flexible and curvilinear fimbriae in only 2 of the 8 highly adhesive strains.